Augmented Reality pada Media Pembelajaran Listrik Statis : Augmented Reality in Static Electricity Learning Media - Gabriela Areros; Yuri Vanly Akay; Brave A. Sugiarso (Universitas Sam Ratulangi, 2025)
Abstract — When two objects rub together or electrons move between them, there is an imbalance of positive and negative charges on one object. This is called static electricity. Based on surveys that have been conducted, it shows that the majority of students in junior high schools have difficulty understanding material and concepts about static electricity. Students feel that the presence of media in the form of learning applications can help in overcoming this problem. Thus, developing learning applications using Augmented Reality (AR) technology offers an interesting solution. This technology can be utilized in the learning process by visualizing a concept or understanding using a virtual object that is projected into the real world so as to provide information that is easy to understand. The system development method used in this research is the Multimedia Development Life Cycle. Based on data obtained from Beta Testing, 67% of respondents experienced an increase in their understanding of static electricity material after using the Static Electricity Learning Application. From these results, Augmented Reality technology can be used as a learning medium to help the learning process become better. Abstrak — Ketika dua objek bergesekan atau elektron berpindah antara mereka, terjadi ketidakseimbangan muatan positif dan negatif di satu objek. Ini disebut listrik statis. Berdasarkan survei yang telah dilakukan menunjukkan sebagian besar siswa di sekolah menengah pertama mengalami kesulitan memahami materi dan konsep tentang listrik statis. Siswa merasa dengan adanya media berupa aplikasi pembelajaran dapat membantu dalam mengatasi masalah tersebut. Dengan demikian Pengembangan aplikasi pembelajaran menggunakan teknologi Augmented Reality (AR) menawarkan solusi yang menarik. Teknologi ini dapat dimanfaatkan dalam proses pembelajaran dengan memvisualisasikan suatu konsep atau pemahaman menggunakan suatu objek virtual yang diproyeksikan dengan dunia nyata sehingga memberikan informasi yang mudah dipahami. Metode pengembangan sistem yang digunakan dalam penelitian ini yaitu Multimedia Development Life Cycle. Berdasarkan data yang diperoleh dari Beta Testing 67% responden mengalami peningkatan pemahaman mengenai materi listrik statis setelah menggunakan Aplikasi Pembelajaran Listrik Statis. Dari hasil tersebut teknologi Augmented Reality dapat dimanfaatkan sebagai media pembelajaran untuk membantu proses belajar menjadi lebih baik.